0220 Role Of CRF Signaling In The Disruption Of Sleep Homeostasis During Chronic Sleep Restriction. (27th April 2018) - Kumar, S; Hsieh, K; McGinty, D; Szymusiak, R
Abstract: Introduction: CSR alters hypothalamic-pituitary-axis (HPA) axis function and can be viewed as a chronic mild stress. Homeostatic responses to sleep loss are present in rats during 1–2 days of CSR, but are attenuated or absent during subsequent days. We hypothesize that elevated corticotropin releasing factor (CRF) signaling in the brain contributes to the attenuation of sleep homeostasis during CSR. In this study we examined the effects of ICV infusion of CRF receptor-1 (CRF-R1) antagonist, in rats subjected to CSR. Methods: CSR was achieved by a forced locomotion on a treadmill (speed=8cm/sec), with a 3/12 sec on/off sequence. This sequence was repeated for 3 hrs, followed by 1 hr sleep opportunity. This 3:1 hr schedule was applied continuously for five days. On CSR day 4, control rats (n=5) received ICV infusion of vehicle (1% DMSO in aCSF) while experimental rats received infusion of either 10 µg (n=7) or 1 µg (n=5) antalarmin (ANT) (0.2 µl/min over 3 hrs starting at ZT6). SWA in NREM sleep (% change from baseline) and time asleep during the 1 hr sleep opportunity at ZT9-10 were analyzed. Results: Compared to baseline, EEG slow-wave activity (SWA) increased in all groups on CSR day 1 (Vehicle; 204 ± 27%, 1ug ANT; 209 ± 9% and 10ug ANT; 216 ± 11). SWA was reduced on CSR day 4 versus day 1 in Vehicle- (144 ± 10% vs 204 ± 27%) and 1 ug ANT- (153 ± 9% vs 209 ± 9% versus) treated rats. Infusion of 10ug ANT on day 4 partially restored the EEG SWA response (187 ± 20% versus 216 ± 11%). Total Sleep Time (TST) on CSR day 1 (in min) was Vehicle; 34.6 ± 3.1, 1ug ANT; 35.6 ± 3.7 and 10ug ANT; 36.7 ± 2.8. On CSR day 3 values were 27.2 ± 2.8, 27.7 ± 6.2, and 28.6 ± 2.7. Infusion of 10 ug ANT on CSR day 4 restored the TST response to sleep loss compared to Vehicle and 1 ug ANT infusion (36.9 ± 2.9 vs 28.7 ± 2.5 vs 27.9 ± 6.3). Conclusion: Findings support the hypothesis that increased CRF signaling in the brain contributes to the suppression of sleep homeostasis during CSR. Support (If Any): VA Merit Award BX00155605 and BX003520.